Prevalensi Asimetri Fungsional pada Murid SD dan SLTP Tarsisius Vireta Tangerang Usia 9 - 16 Tahun - Cathy Kadharmestan; Maria Purbiati; Haru S. Anggani (Faculty of Dentistry, Universitas Indonesia, 2013)
The objectives of this study were to determine the prevalence of functional asymmetry in elementary and junior high school Tarsisius Vireta Tangerang students from 9 to 16 years old, and to determine which age group has the most extensive functional asymmetry. The subjects were grouped based on the development of the first molar until the second molar, as follows: group of age 9 to 11 years old, age above 11 to 14 years old, and age above 14 to 16 years old. Functional examination was done with a modified Castaldi method. The results showed that overall, functional asymmetry was found in 18 out of 306 subjects (prevalence 5.88%) who were examined. From the age group of 9 to 11 years old, there were 8 such subjects (7.14%); from the age group of above 11 to 14 years old, 7 subjects (6.73%); from the age group of above 14 to 16 years old, there were 3 subjects (3.33%). Therefore, the age group of 9 to 14 years old was showing most frequent functional asymmetry. It was also found that most subjects that experienced functional asymmetry, especially in anteroposterior direction, were subjects with class III malocclusion. In general, subjects with functional asymmetry had crowding and premature contact - which could happen at almost any tooth, but mostly at the incisors. DOI: 10.14693/jdi.v15i1.81